ANTIBACTERIAL ACTIVITY OF CHITOSAN AND HYDROLYZED COCONUT OIL AND THEIR COMBINATION AGAINST BACILLUS CEREUS AND ESCHERICHIA COLI - Silalahi, Jansen; Situmorang, Petrika; Patilaya, Popi; Ce Silalahi, Yosy (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: The purpose of this study was to evaluate the antibacterial activity of chitosan, hydrolyzed coconut oil and their combination against Bacillus cereus and Escherichia coli. Methods: The materials used in this study were powder of chitosan (obtained from prawn shell produced by Laboratory of Research Centre FMIPA University of Sumatera Utara) and virgin coconut oil (VCO) product of Siti Nurbaya-Indonesia. VCO was partially hydrolyzed by Lipozyme TLÂ® IM (active at sn-1,3 position) and the result called hydrolyzed virgin coconut oil (HVCO). The bacteria used in this study were B. cereus and E. coli. The antibacterial activity of chitosan in 1% acetic acid and HVCO in dimethylsulfoxide was tested by Kirbyâ€“Bauer agar diffusion method using paper disc with diameter of 6 mm. Results: The results showed that the minimum inhibitory concentration of chitosan against B. cereus and E. coli is at concentration of 0.05% with inhibition zone diameter of 6.86 mm and 7.56 mm, respectively. MIC of HVCO against B. cereus is at concentration of 0.25% with inhibition zone diameter of 6.40 mm, and against E. coli is at a concentration of 0.50% with inhibition zone diameter of 6.20 mm. The inhibition zone diameter of chitosan 0.05% and HVCO 0.25% in combination against B. cereus is 8.33 mm which is higher than half the sum of chitosan 0.05% and HVCO 0.25% (6.63 mm). The inhibition zone diameter of chitosan 0.05% and 0.5% HVCO in combination against E. coli is 8.53 mm which is higher than half the sum of chitosan 0.05% and HVCO 0.5% (6.53 mm). Conclusion: The findings of this study indicate that chitosan is more antibacterial than HVCO, and the interaction between chitosan and HVCO in combination demonstrated to be synergistic against B. cereus and E. coli. Keywords: Antibacterial, Chitosan, Coconut oil, Combination, Bacillus cereus, Escherichia coli